EFEK SUPLEMENTASI DHA TERHADAP STATUS NUTRISI DAN PERTUMBUHAN BAYI PADA PERIODE AWAL KEHIDUPAN - Kholifatul Ummah; Rakhmalia Imeldawati; Ida Susila; Bilqis NurMustofa (Jurnal Medicare, 2025)
Background: The early life period of 0–6 months is a crucial phase in child growth and development, where infant nutritional needs are highly dependent on the quality of breast milk. Docosahexaenoic acid (DHA) plays a role in supporting infant growth and development, but evidence on the effect of DHA supplementation on infant growth is still variable. Objective: To analyze the effect of DHA supplementation in breastfeeding mothers on infant nutritional status and growth in early life. Methods: This study used a quasi-experimental design with a one-group pretest–posttest approach. The subjects were breastfeeding mothers with infants aged 0–6 months. The intervention was performed by providing DHA supplementation to breastfeeding mothers. Infant nutritional status and growth were assessed based on body weight, body length, and z-scores for BB/A and PB/A according to WHO standards. Data were analyzed using paired statistical tests. Results: DHA supplementation in breastfeeding mothers showed a trend towards improved infant nutritional status and growth, characterized by increased body weight, body length, and improvements in anthropometric z-scores. Conclusion: DHA supplementation in breastfeeding mothers has the potential to support infant growth without disrupting exclusive breastfeeding practices and can be considered as a nutritional intervention in primary health care.